Caracterização genética de porta-enxertos de videira empregando marcador molecular RAPD - Capel, Lívia Santos (2008)
Identification of several vine rootstocks by phenomenological traits lacks security and has brought about certain problems for vine cultivators. In current analysis RAPD (Random Amplified Polymorphic DNA) characterizes several rootstocks of vine planted in the northern and northwestern regions of the state of Paraná. Results may be useful to explain identification of these varieties. DNA of rootstock varieties 420-A, Schwarzmann, IAC-766 - Campinas, Traviú, Kober 5BB, and IAC-572 - Jales has been extracted and amplified by 17 primers. The 247 fragments assured total polymorphism (87.04%) for these varieties. Differential frequency for amplified fragments determined a 0.7094 genetic divergence between the rootstocks. Highest genetic identity (83.22%) has been detected between IAC-766-Campinas and Schwarzmann (83.22%) and the lowest (61.96%) between Kober 5BB and 420-A. Dendrogram also identified a group made up of varieties 420-A, Schwarzmann and IAC-766 - Campinas. Rottstocks Traviú, IAC-572 - Jales and Kober 5BB did not make up groups and thus showed high divergence among them. DNA amplification by primers OPB-4, OPB-5 and OPP-17 produced fragments which were specific to rootstocks 420-A and IAC-512 - Jales; primers OPB-1, OPB-3, OPB-4 and OPB-11 produced fragments specific to Kober 5 BB. Specific fragments may be used as markers for genotype IAC-522 - Jales, 420-A and Kober 5BB. The frequently mixed up varieties Kobber 5BB and 420-A may actually be distinguished on a molecular basis.